2014
DOI: 10.1186/2051-6673-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Early experience, structural dissociation, and emotional dysregulation in borderline personality disorder: the role of insecure and disorganized attachment

Abstract: Persistent problems in emotional regulation and interpersonal relationships in borderline patients can be understood as developing from difficulties in early dyadic regulation with primary caregivers. Early attachment patterns are a relevant causal factor in the development of Borderline Personality Disorder (BPD).Links between attachment issues, early history of neglect, and traumatic experiences, and symptoms observed in patients with BPD as per the DSM-5 classification (American Psychiatric Association: Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 43 publications
5
36
0
1
Order By: Relevance
“…For some, the idea that BPD might have an underlying biological and genetic basis came as a surprise. It is our experience from the UK‐service setting that BPD is largely understood within a psychological trauma‐informed paradigm in which it is seen as inherently linked with adverse childhood experiences including childhood sexual abuse (Menon, Chaudhari, Saldanha, Devabhaktuni, & Bhattacharya, ), severe neglect, attachment ruptures, overprotection and invalidating environments (Mosquera, Gonzalez, & Leeds, ). While The Science of BPD in no way diminishes the importance of historical trauma, it also links this with predisposing biological factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some, the idea that BPD might have an underlying biological and genetic basis came as a surprise. It is our experience from the UK‐service setting that BPD is largely understood within a psychological trauma‐informed paradigm in which it is seen as inherently linked with adverse childhood experiences including childhood sexual abuse (Menon, Chaudhari, Saldanha, Devabhaktuni, & Bhattacharya, ), severe neglect, attachment ruptures, overprotection and invalidating environments (Mosquera, Gonzalez, & Leeds, ). While The Science of BPD in no way diminishes the importance of historical trauma, it also links this with predisposing biological factors.…”
Section: Discussionmentioning
confidence: 99%
“…For some, the idea that BPD might have an underlying biological and genetic basis came as a surprise. It is our experience from the UK-service setting that BPD is largely understood within a psychological trauma-informed paradigm in which it is seen as inherently linked with adverse childhood experiences including childhood sexual abuse (Menon, Chaudhari, Saldanha, Devabhaktuni, & Bhattacharya, 2016), severe neglect, attachment ruptures, overprotection and invalidating environments (Mosquera, Gonzalez, & Leeds, 2014 BPD-diagnosed individuals seem to feel is required actually improve care, or is it an impossible demand whose purpose is largely to shift responsibility for changing practice onto "the system"? Some nurses appeared resistant to change from the outset, maintaining an adverse attitude towards BPD-diagnosed patients which led to frustration when the training did not validate that.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, individuals with Borderline Personality Disorder have deficits in accurately attributing mental states to others (cognitive empathy) and having an appropriate emotional response to another person’s emotional state (emotional empathy) (Preissler et al 2010; Roepke et al 2012). These deficits relate to a theory of mind deficit possibly related to insecure and disorganized early attachment (Mosquera et al 2014). …”
Section: The Neuropsychology Of Psychiatric Disorders Vs Alcoholismmentioning
confidence: 99%
“…Twin studies have indicated that monozygotic twins have significantly higher concordance rates than dizygotic twins for AN, indicating there is a genetic component to the development of AN [1]. Neurologic and hormonal changes associated with malnourishment may also play a role in the maintenance AN [6,7].…”
Section: Issn: 2056-8339mentioning
confidence: 99%
“…The Diagnostic and Statistical Manual of Mental Disorders, 5 th Edition defines anorexia nervosa (AN) as the restriction of energy intake relative to requirements leading to significantly low body weight, in conjunction with an extreme fear of gaining weight and a distorted view of body weight and shape [1]. AN is defined as either restricting type (AN-R) or binge-eating/purging type (AN-BP).…”
Section: Introductionmentioning
confidence: 99%